Tathbiq Ta'lim al-Lughat al-'Arabiyyah 'Ala Asas Anmath al-Jumal li al-Thullab al-Hashilin 'Ala al-Minah BIDIKMISI - Zubaidah Zubaidah (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2018)
Learning qawaid nahwu (Arabic Grammar) is often considered difficult, especially for beginners in learning Arabic, even many people consider that Arabic is difficult. Learning Arabic for students who receive Bidik Misi scholarships for example, because these students come from different scientific backgrounds and schools and most of them are beginners and have never studied Arabic, therefore special methods and strategies are needed that are different from students who are have learned Arabic even from Pondok Pesantren. There are various ways and strategies used to overcome these difficulties, including by increasing the practice of simple and easy sentence patterns. The lecturer gives examples to students in the form of simple sentence patterns, then students can copy and then create new sentence patterns so that they can easily understand the qowa'id nahwu. For this reason, in this paper, it is explained the importance of understanding simple sentence patterns and examples of making sentences through sentence patterns for students who receive Bidik Misi scholarships at IAIN Bukittinggi.